Answer:
f(x+y) = f(x)+f(y)
f(cx)=c(f(x)), for ∀x,c ∈ R
Therefore f is a linear transformation.
Step-by-step explanation:
Linear transformation:
Let a and b be two vector space over some field R. A function f: A→B is said to be linear transformation if for any two vectors a, b∈ A and any scalar c∈ R such that
(i)f(a+b) = f(a)+ f(b)
(ii) f(ca)= cf(a)
Here the function is f(x)= <6x,-6x,-9x>
Then f(y) = <6y,-6y,-9y> [ putting x= y in the function]
(i)
f(x+y)
= <6(x+y),-6(x+y),-9(x+y)>
f(x)+f(y)
=<6x,-6x,-9x> + <6y,-6y,-9y>
=<6x+6y,-6x-6y,-9x-9x>
=<6(x+y),-6(x+y),-9(x+y)>
Therefore f(x+y) = f(x)+f(y)
(ii)
c(f(x))
=c<6x,-6x,-9x>
f(cx)
=<6cx,-6cx,-9cx>
=c<6x,-6x,-9x>
Therefore f(cx)=c(f(x)), for ∀x,c ∈ R
Therefore f is a linear transformation. Since it satisfies the two condition.